Empirical Bayes Inference for the Parameter of Power Distribution Based on Ranked Set Sampling - Naiyi Li; Yuan Li; Yongming Li; Yang Liu (Discrete Dynamics in Nature and Society)
This research is based on ranked set sampling. Through the analysis and proof, the empirical Bayes test rule and asymptotical property for the parameter of power distribution are obtained.